Psychoactive substance as a predictor of well-being of young adults in selected market areas in Ibadan North Local Government Area (2022)
Recent events in Nigeria seem to suggest that young people are being indoctrinated and used under the influence of psychoactive substances to perpetuate various crimes including terrorism. There is need to examine and control the use of these substances in order to prevent escalation of these maladies. This study examined psychoactive substance as a predictor of well-being of young adults in selected market areas in Ibadan North Local Government Area, Oyo State. The study adopted descriptive survey research design. The population comprises of 150 young adults in selected market areas. A purposive sampling technique was employed in selecting 30 respondents from each of the five markets in the study area, five markets area were selected because they were notorious for peddling substance hoarding. A structures questionnaire for data collection was used. The hypotheses were analyzed using Pearson Product Moment Correlation. The result shows that there is no significant relationship between psychoactive substance and alcohol use and physical well-being of young adults in selected market areas (r = ,044, n=143,p(. 602)>.05). The result further shows that there is a significant relationship between psychoactive substance and alcohol use and psychological well- being(r = .326, n-143, p(.000)<.05).Finally, the result shows that there is a significant relationship between psychoactive substance and alcohol use and social well-being of young adults in selected market area (r = .284, n=143,p(.001)<.05). The study recommends that public enlightenment on the detrimental effects of psychoactive substances should be strategically targeted to include community, market areas, family unit, primary and secondary school children.